Survival and Feeding Behavior of Diaphorina citri (Hemiptera: Liviidae) Adults on Common Cover Crops in Citrus - Justin George; Ramdas Kanissery; Mahesh Bashyal; Blessy Tamayo; Lukasz L. Stelinski (Agriculture, 2022)
Asian citrus psyllid, Diaphorina citri, transmits Candidatus Liberibacter asiaticus (CLas), the bacterial pathogen responsible for citrus greening disease. To explore the possibility that cover crops in citrus groves may serve as refuges for this pathogen vector during unfavorable host conditions, psyllid feeding was investigated on six common cover crop species and citrus using electrical penetration graph (EPG) recordings and behavioral bioassays. EPG recordings showed that the proportion of time spent by D. citri feeding on xylem was similar or higher on all tested cover crops (17%–32%) compared to the positive control (12%), the preferred host, Citrus macrophylla. Very little to no phloem feeding was observed on cover crops by the adults. In the choice assays, more D. citri adults settled on buckwheat (Fagopyrum esculentum) and cowpea (Vigna unguiculata) than on the host, C. macrophylla, 24 h after release. No-choice assays showed that the citrus cover crop species evaluated extend the survival of D. citri up to 8 d because of xylem feeding. Our results indicate that some cover crop species may be less suitable refuge sites for D. citri than others, but none served as breeding sites or supported more than 8 d of survival.